2011
DOI: 10.3928/00989134-20110106-01
|View full text |Cite
|
Sign up to set email alerts
|

Work Organization and Health Issues in Long-Term Care Centers

Abstract: This qualitative study explored common and divergent perceptions of caregivers and managers regarding occupational health and safety, work organization, and psychosocial concerns in long-term care centers. Both common and differing issues were identified. Both groups agreed on the importance of ergonomic concerns, the high prevalence of stress, and receptiveness to participatory health promotion programs. However, numerous work organization issues and physical and psychosocial workplace hazards were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…The high turnover rate in nursing homes (Donoghue, 2010) and tight staffing levels (Feuerberg, 2001) are well documented and create a vicious cycle because they contribute to work strain among employees, which in turn increases turnover (Zhang, Punnett, & Gore, 2014). Psychosocial stress had already been documented as a prevalent concern in all three of these centers (Zhang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high turnover rate in nursing homes (Donoghue, 2010) and tight staffing levels (Feuerberg, 2001) are well documented and create a vicious cycle because they contribute to work strain among employees, which in turn increases turnover (Zhang, Punnett, & Gore, 2014). Psychosocial stress had already been documented as a prevalent concern in all three of these centers (Zhang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, nursing homes have high employee turnover (Trinkoff et al, 2013), posing challenges for staffing levels (Shin, 2013) and resulting in poor resident outcomes and quality of life (Shin, 2013; Trinkoff et al, 2013). Nursing home employees experience high physical workloads and stressful psychosocial work environments (Lapane & Hughes, 2007; Zhang et al, 2011), leading to a range of health problems, such as musculoskeletal disorders, cardiovascular diseases, and poor mental health (Miranda, Gore, Boyer, Nobrega, & Punnett, 2015; Punnett et al, 2009). …”
mentioning
confidence: 99%
“…Despite the fact that most older people want to live in their own homes for as long as possible (de Bruin et al, ; Turjamaa, Hartikainen, Kangasniemi, & Pietilä, ), some dislike it because they feel that their home is a lonely and unsafe environment. Therefore, it is essential to take into account older people's rights to make decisions about their own lives (Jacobs, ; Zhang et al, ). Smart home systems can help older people, but they also pose significant ethical challenges, such as privacy, autonomy, dignity, safety and trust, and it is important to consider these issues (Sánchez, Taylor, & Bing‐Johnsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Logistical feasibility of team meetings was considered as an essential precursor for the implementation of workplace intervention, especially because time strain had been identified previously as a challenge (Zhang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Assessment of shared interest and commitment between managers and employees are important for successful implementation of a workplace intervention (Weiner, 2009). However, employees’ perceptions of occupational safety and health risks, the participatory culture, and the decision-making power may be different from those of managers (Zhang et al, 2011). Weiner (2009) suggested that a discrepancy between current and desired conditions, and an appealing vision of the future, could indicate the organization’s readiness for change in terms of the degree to which employees perceive the change as needed, important, or worthwhile.…”
Section: Discussionmentioning
confidence: 99%